Impact of oil price fluctuation on comparative advantage of manufacturing sectors in ASEAN-5 - Noor Aida, Noh (2021)
In the ASEAN-5 economy, the manufacturing sector contributes more than 30 percent to Gross Domestic Product and its performance affects ASEAN-5’s comparative advantage. Even though there are studies found a significant impact of oil price fluctuations on economic activities, but effect on comparative advantage is largely ignored. Therefore, this study attempts to fill the gap of oil price fluctuations and comparative advantage in ASEAN-5 manufacturing sector for the period of 1991 to 2018. More specifically, it aims to evaluate the effects of oil price fluctuations on comparative advantage, the factors affecting changes in comparative advantage, and the dynamic changes in comparative advantage. The Seemingly Unrelated Regression (SURE), Probit model, Spearman rank correlation coefficient (SRC) are employed in this study. Using SURE model, oil price fluctuations adversely affect the comparative advantage of most manufacturing commodities in all technological classification of export. Results of the estimated Probit model, reveal that changes in the factors 1 (real gross domestic product, manufacturing value added, capital, foreign direct investment), factors 2 (labour, oil demand, research and development) and factors 3 (real oil price domestic, trade openness) have significant effects on the changes in comparative advantage. The findings from SRC reveal that there are dynamic changes in the rank of commodities in terms of comparative advantage. It is concluded that measuring competitiveness of manufacturing commodities using technological classification of export is crucial to focus on the products with high trade growth which could facilitate better economic growth in the future. The implementation of effective policy should be given serious consideration to ensure the comparative advantage is not affected by oil price fluctuations. ASEAN-5 needs to monitor the price of oil to ensure that unstable price will not harm the comparative advantage.